Kepek Village Information System, Wonosari District, Gunungkidul Regency - Bima Respati; Riyan Abdul Aziz (Formosa Journal of Science and Technology, 2023)
This study aims to describe the development and implementation of the Village Information System (SID) in Kepek Village, Wonosari District, Gunungkidul Regency. The research method used is a qualitative approach with a case study design. Data was collected through interviews with related parties, observation, and analysis of documents related to SID. The results showed that Kepek Village has rich natural and cultural potential, but the management of information about village development potential and programs is still not optimal. SID development began in 20XX with a participatory approach, involving village communities and related parties in the development process.